2008
DOI: 10.1111/j.1558-5646.2008.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

GENETICS OF DROUGHT ADAPTATION INARABIDOPSIS THALIANAII. QTL ANALYSIS OF A NEW MAPPING POPULATION, KAS-1 × TSU-1

Abstract: Despite compelling evidence that adaptation to local climate is common in plant populations, little is known about the evolutionary genetics of traits that contribute to climatic adaptation. A screen of natural accessions of Arabidopsis thaliana revealed Tsu-1 and Kas-1 to be opposite extremes for water-use efficiency and climate at collection sites for these accessions differs greatly. To provide a tool to understand the genetic basis of this putative adaptation, Kas-1 and Tsu-1 were reciprocally crossed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
132
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(140 citation statements)
references
References 90 publications
(129 reference statements)
5
132
1
Order By: Relevance
“…Quantitative trait locus (QTL) mapping and global gene expression analyses are useful methods to assess the genetic basis of traits involved in drought adaptation (McKay et al, 2008;Hall et al, 2010;Juenger et al, 2010;Des Marais et al, 2012;Schmalenbach et al, 2014;El-Soda et al, 2015). In particular, the genomic perturbation of experimental crosses utilizes recombination to break up linkage disequilibrium and allows causal inference of how variation at a given locus leads to phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait locus (QTL) mapping and global gene expression analyses are useful methods to assess the genetic basis of traits involved in drought adaptation (McKay et al, 2008;Hall et al, 2010;Juenger et al, 2010;Des Marais et al, 2012;Schmalenbach et al, 2014;El-Soda et al, 2015). In particular, the genomic perturbation of experimental crosses utilizes recombination to break up linkage disequilibrium and allows causal inference of how variation at a given locus leads to phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%
“…The timing and duration of water limitation, as well as other environmental variables, all influence drought-adaptation strategies used by plants. Thus, we may expect substantial natural variation of these traits within a widely distributed species, such as Arabidopsis (7)(8)(9)(10), with many of these differences related to the local conditions to which a particular accession has adapted (11)(12)(13). Several studies have identified quantative trait loci (QTL) controlling differences in metabolite content (14)(15)(16)(17)(18), but such studies have yet to be extended to drought-induced metabolic changes, such as proline accumulation.…”
mentioning
confidence: 99%
“…
Studies in A. thaliana reported a genomic region responsible for drought avoidance co-130 mapping with a region contributing to a constitutively lowered Tr and simultaneously 131 leading to an enhanced TE (Masle et al 2005;McKay et al 2008). Following these 132 examples, our current hypothesis is that only critical portions of the large DT-QTL, 133 linked to specific mechanisms, matter for the terminal drought tolerance of pearl millet 134 and these needs to be accurately mapped to enhance the precision of marker assisted 135 introgression.
…”
mentioning
confidence: 99%